Design optimization of the cooling lines in plastic injection molds - Balingit, Wilbert H. (2008)
In the design of plastic injection molds, achieving uniform mold cooling is recognized as an important part. Since experimentation after the mold is built is expensive in terms of time, personnel and money, the provision of suitable and adequate cooling arrangements is an important aspect of mold design. The development of design guidelines for the determination of the optimum locations and sizes of cooling lines, that would ensure the uniform mold wall temperature distributions and minimize the deformations in the mold wall, is of great importance to the mold designers. Optimization of the locations, arrangement and sizes of the cooling lines in plastic injection molds were conducted using the steepest descent method. The line search method used in the determination of the step size was the integrated bracketing and golden section method. To obtain an approximate expression for the gradient vector, the Newton's forward difference formula was used. Modeling and analysis of the three-dimensional plastic injection molds were conducted using the SolidWorks software. SolidWorks uses the Finite Element Method (FEM) to simulate the working conditions of designs and predict their behavior. In order to determine the temperature distribution along the mold cavity surface, transient heat transfer or thermal analysis were conducted. The local deformations at the mold cavity surface under the action of the injection pressure and the thermally induced displacements caused by the temperature gradient were determined by the thermo-elastic static analysis. Final designs were obtained at the end of the optimization process. General design guidelines were developed for the optimum cooling of plastic injection molds for acrylonitrile-Butadiene-Styrene (ABS) and Polyamide (PA) of the type Nylon 6/6 as product moldings with part wall thicknesses of 1 mm, 2 mm, and 3 mm.
Thesis (M.S. Mechanical Engineering)--University of the Philippines, Diliman.
Keywords: Injection molding of plastics